Application Green Accounting To Sustainable Development Improve Financial Performance Study In Green Industry - Justita Dura; Riyanto Suharsono (Jurnal Akuntansi, 2022)
The research of this study is to determine the impact of green accounting on sustainable development and financial performance, as well as the impact of financial performance on sustainable development and green accounting on sustainable development through financial performance. In this study, the population is a manufacturing company that implements the green industry and is registered with the Indonesian Stock Exchange between 2017 and 2020. Purposive sampling was used to acquire data from 39 different companies. Path analysis was performed to analyze the data. Green accounting hurts sustainable development, green accounting has no impact on financial performance, financial performance has no impact on sustainable development, and green accounting has a financial performance impact on sustainable development.